Characteristics and prognosis of patients with elevated triglycerides in acute myocardial infarction: observational data from a large database over a 17 years period. (14th October 2021) - Zeller, M; Chague, F; Maza, M; Bichat, F; Beer, J C; Masson, D; Cottin, Y; Farnier, M; ,
Abstract: Background and aim: From a large database of a regional registry, we aimed to address the prevalence, characteristics and prognosis of patients with elevated triglycerides (TG) in patients hospitalized for an acute myocardial infarction (MI). Methods: From the multicenter database (RICO survey), all consecutive patients hospitalized for an acute MI (2001–2017) and alive at discharge were included. Patients with TG >500 mg/dL, lost to follow-up (FU), or under chronic fibrate treatment were excluded. Patients with high TG (>200 mg/dL) on admission were compared to those with TG ≤200 mg/dL. Endpoints were recurrent ischemic events (i.e. recurrent MI, angina, unstable angina, stroke or urgent revascularization (PCI or CABG)) at 1-year FU. Results: Among the 10667 patients included, 1886 (17.7%) had elevated TG. When compared with patients with TG ≤200 mg/dL, patients with high TG were younger (59 vs 69 y, p<0.001), had a higher BMI (28 vs 26 kg/m 2, p<0.001), were more frequently men (77 vs 68%, p<0.001), diabetic (27 vs 21%, p<0.001), and smokers (42 vs 28%, p<0.001). The rate of statin therapy at discharge was similar for the 2 groups (79 vs 77%, p=0.285), as well as SYNTAX score and rate of multivessel disease (p=0.368 and p=0.791). In high TG group, LDL cholesterol was higher (130 vs 120 mg/dL, p<0.001) and HDL-cholesterol was lower (37 vs 46 mg/dL). At 1-Y FU, recurrent ischemic events were more frequent in elevated TG patients (11.2 vs 9.1%, p=0.004). In multivariate logistic regression analysis, high TG (OR (95% CI): 1.356 (1.095–1.679)) remains an independent estimate for recurrent ischemic event, even after adjustment for confounding (GRACE score, diabetes, obesity). Conclusions: In our large population-based cohort, elevated TG are common in acute MI, and associated with residual risk of recurrent ischemic events, beyond traditional prognostic markers. Our data may help to identify candidates for targeted therapies to reduce recurrent ischemic risk after MI. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Amarin